2017
DOI: 10.2147/opth.s144985
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular pressure 1 year after vitrectomy in eyes without a history of glaucoma or ocular hypertension

Abstract: ObjectiveThe aim of this study was to investigate the incidence, risk factors, and treatment of elevated intraocular pressure (IOP) 1 year after vitrectomy in eyes without a history of glaucoma or ocular hypertension.Patients and methodsThis retrospective study comprised 256 eyes from 256 consecutive patients without a history of glaucoma or ocular hypertension who underwent vitrectomy and were followed up for 1 year. The incidence of elevated IOP at 1 year after vitrectomy was calculated. We compared the char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 30 publications
2
31
0
Order By: Relevance
“…Regarding the characteristics of a longer globe, thinner lamina cribrosa, compromised autoregulatory control of ocular hemodynamics and thinner scleral wall with different elasticity, even a transient IOP increase or fluctuation during the vitrectomy may be sufficient to cause damage. Furthermore, there is increasing evidence that high myopia and vitrectomy themselves may be a risk factor for development or worsening of glaucoma (Fang et al 2017). Thus, shortening the operation time, reducing the IOP fluctuation during the vitrectomy and careful perioperative IOP monitoring are required to manage these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the characteristics of a longer globe, thinner lamina cribrosa, compromised autoregulatory control of ocular hemodynamics and thinner scleral wall with different elasticity, even a transient IOP increase or fluctuation during the vitrectomy may be sufficient to cause damage. Furthermore, there is increasing evidence that high myopia and vitrectomy themselves may be a risk factor for development or worsening of glaucoma (Fang et al 2017). Thus, shortening the operation time, reducing the IOP fluctuation during the vitrectomy and careful perioperative IOP monitoring are required to manage these patients.…”
Section: Discussionmentioning
confidence: 99%
“… 21 24 In our previous study, we reported that about 20% of the patients who underwent PPV at our hospital in November 2011 had no history of glaucoma or ocular hypertension, but suffered ocular hypertension during the first postoperative year. 6 Most ocular hypertension occurs in the first month after PPV. 6 Risk factors for ocular hypertension after PPV include a history of glaucoma, a history of diabetes mellitus, scleral buckling procedures, lensectomy, and the use of silicone oil or expanding gas.…”
Section: Discussionmentioning
confidence: 99%
“… 6 Most ocular hypertension occurs in the first month after PPV. 6 Risk factors for ocular hypertension after PPV include a history of glaucoma, a history of diabetes mellitus, scleral buckling procedures, lensectomy, and the use of silicone oil or expanding gas. 6 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations